(untitled) (Ameghiniana, 2013)
Two new records of Pediolagus salinicola (Burmeister, 1875) from the late Pleistocene of the Buenos Aires province are described. Both records are located to the south and the east of the recent area of distribution of that species. They confirm the existence of arid climatic conditions in the Buenos Aires province during the late Pleistocene.